'Ulum Al-Qur'an Instruction: Urgency, Problem Diagnosis, and Important Things to Fix it - Kurniawan, Syamsul; Fitriyani, Feny Nida; Toktayong, Usman (Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) IAIN Pontianak, 2024)
The focus of this article is the urgency, problem diagnosis, and important things to fix problems in 'Ulum Al-Qur'an lectures. This article is sourced from the results of qualitative-descriptive research because this research only aims to explore as deeply as possible the social facts that the author has studied in the field, and then depict or describe the facts in the field objectively according to the author's needs as they are. The object of this research is students in the Islamic Religious Education Study Program, Faculty of Tarbiyah and Teacher Training, IAIN Pontianak. Thus, the setting of this research is the Islamic Religious Education Study Program, Faculty of Tarbiyah and Teacher Training, IAIN Pontianak. The results of the author's research show: one, the importance of studying the 'Ulum Al-Qur'an in the Islamic Religious Education Study Program, because of the importance of this discipline to equip students in Islamic universities with the sciences of the Al-Qur'an, so that they are not only able to read but also understand it. Two, the time allocation given to the 'Ulum Al-Qur'an lectures and the learning methods that tend to be conventiona, they were diagnosed as the cause of the failure of the 'Ulum Al-Qur'an lectures given in the Islamic Religion Education Study Program, Faculty of Tarbiyah and Teacher Training, IAIN Pontianak. Three, to overcome this problem, apart from increasing the time allocation for 'Ulum Al-Qur'an lectures, there is also a need to change the paradigm of 'Ulum Al-Qur'an lectures at IAIN Pontianak from teacher-centered learning to student-centered learning. Lecturers must also not get bored of motivating their students to repeat learning outside of the class on the material presented in class. Apart from that, it is also important to pay attention to how the syllabus and semester learning plans are designed by considering multidisciplinary, interdisciplinary and even transdisciplinary approaches so that the material does not tend to be textual but rather contextual.Fokus tulisan ini adalah urgensitas, diagnosa masalah, dan hal-hal penting untuk memperbaiki masalah dalam perkuliahan ‘Ulum Al-Qur‘an. Tulisan ini bersumber dari hasil penelitian kualitatif-deskriptif karena penelitian ini hanya bertujuan untuk menggali sedalam-dalamnya fakta sosial yang penulis dalami di lapangan, dan kemudian menggambarkan atau mendeksripsikan fakta di lapangan tersebut secara objektif sesuai kebutuhan penulis secara apa adanya. Objek penelitian ini adalah mahasiswa di Program Studi Pendidikan Agama Islam, Fakultas Tarbiyah dan Ilmu Keguruan, IAIN Pontianak. Dengan demikian, setting penelitian ini adalah di Program Studi Pendidikan Agama Islam, Fakultas Tarbiyah dan Ilmu Keguruan, IAIN Pontianak. Hasil penelitian penulis menunjukkan: satu, pentingnya 'Ulum Al-Qur'an dipelajari di Program Studi Pendidikan Agama Islam, karena pentingnya disiplin ilmu ini untuk membekali mahasiswa di perguruan tinggi Islam dengan ilmu-ilmu Al-Qur'an, sehingga agar mereka tidak hanya mampu membaca tetapi juga memahaminya. Dua, Alokasi waktu yang diberikan pada mata kuliah ‘Ulum Al-Qur’an dan metode pembelajaran yang cenderung konvensional oleh dosen ‘Ulum Al-Qur’an, didiagnosis sebagai penyebab kegagalan perkuliahan ‘Ulum Al-Qur’an yang diberikan di Program Studi Pendidikan Agama Islam, Fakultas Tarbiyah dan Ilmu Keguruan, IAIN Pontianak. Tiga, untuk mengatasi masalah tersebut, kecuali penambahan alokasi waktu perkuliahan ‘Ulum Al-Qur’an, juga perlu adanya perubahan paradigma perkuliahan ‘Ulum Al-Qur’an di IAIN Pontianak, yaitu dari teacher centered learning menjadi student centered learning. Dosen pengampu juga mesti tak bosan-bosannya memotivasi mahasiswanya untuk mengulang belajar di luar kelas tentang materi yang disampaikan di kelas. Selainnya, penting juga diperhatikan penyusunan silabus dan rencana pembelajaran semester dirancang dengan mempertimbangkan pendekatan multidisipliner, interdisipliner, dan bahkan transdisipliner sehingga materinya tidak cenderung tekstual melainkan kontekstual.